A clinico-epidemiological study of eczematous dermatoses in the geriatric population in a tertiary care hospital - Khan, Farhat; Nayak, Chitra (International Journal of Research in Dermatology, 2024)
Background: Eczema being widespread in India, not much research has been done on the clinico-epidemiological profile of eczemas or their potential association with other comorbidities. The study’s objective was to determine the clinico-epidemiological profile of eczematous dermatoses in the elderly population and any potential relationships to risk factors and comorbidities. Methods: It was an observational cross-sectional analytical time bound clinico-epidemiological study which was conducted in the dermatology out-patient department of Topiwala National Medical College and B.Y.L. Nair hospital in Mumbai, Maharashtra, between March 2019 and September 2020. Parameters recorded were age, gender, occupation, onset, duration, and progression of diseases, aggravating and relieving factors, associated chronic medical, surgical, and skin conditions. Also, history of atopy, sun exposure and irritant application were taken. Results: Of the patients receiving out-patient care, 1.67% had eczema. Among 50 study patients, mean age was 70.02 years in males and 69.78 years among females. With 27.03% of patients, asteatotic and chronic eczema were the most prevalent kinds of eczema. In our study, we found a significant association (p=0.016) between hypertension and different forms of eczema, with chronic eczema being more common in hypertensive patients (80%). Most common comorbidity was diabetes, seen in 58% of patients with significant association (p=0.024) and asteatotic eczema being the most common form. There was a significant correlation (p=0.036) observed between eczema and various nail findings associated with eczema. Conclusions: Appropriate management of eczema is important in alleviating problems faced by the geriatric populations.